A novel method for monitoring the constancy of beam path accuracy in CyberKnife1. Issue 5 (19th April 2019) - Yang, Bin; Wong, Wing Kei Rebecca; Lam, Wai Wang; Geng, Hui; Kong, Chi Wah; Cheung, Kin Yin; Yu, Siu Ki
Abstract: The aim of current work was to present a novel evaluation procedure implemented for checking the constancy of beam path accuracy of a CyberKnife system based on ArcCHECK. A tailor‐made Styrofoam with four implanted fiducial markers was adopted to enable the fiducial tracking during beam deliveries. A simple two‐field plan and an isocentric plan were created for determining the density override of ArcCHECK in MultiPlan and the constancy of beam path accuracy respectively. Correlation curves for all diodes involved in the study were obtained by analyzing the dose distributions calculated by MultiPlan after introducing position shifts in anteroposterior, superoinferior, and left–right directions. The ability of detecting systematic position error was also evaluated by changing the position of alignment center intentionally. The one standard deviation (SD) result for reproducibility test showed the RMS of 0.054 mm and the maximum of 0.263 mm, which was comparable to the machine self‐test result. The mean of absolute value of position errors in the constancy test was measured to 0.091 mm with a SD of 0.035 mm, while the root‐mean‐square was 0.127 mm with a SD of 0.034 mm. All introduced systematic position errors range from 0.3 to 2 mm were detected successfully. Efficient method for evaluating the constancy of beam path accuracy of CyberKnife has been developed and proven to be sensitive enough for detecting a systematic drift of robotic manipulator. Once the workflow is streamlined, our proposed method will be an effective and easy quality assurance procedure for medical physicists.